Alat pemberian pakan kucing otomatis berbasis arduino uno - Sudirman, Muh. Arwan; Muhallim, Muhlis; Sulaeman, Budiawan (Computer Science and Information Technology, 2024)
This research is motivated by the need for a more practical and systematic cat feeding device. Irregularities in feeding cats can have negative impacts on their health, such as digestive problems and malnutrition. The aim of this study is to design and develop an automatic cat feeder that effectively regulates feeding according to predetermined times. The method used is the prototype method, which includes stages such as data collection, planning, design, prototype development, and testing. This device uses Arduino Uno as the main controller, with additional components such as an RTC to set feeding schedules, a servo motor to open and close the food container, a load sensor to measure the food weight, and a buzzer as an alarm when food runs low. The system also utilizes a solar panel as a power source. The results show that the automatic cat feeder functions as expected, capable of delivering food on time and in the desired portions. Additionally, the device operates well using solar power as its main energy source.